Composites of polypropylene/Candelilla fiber (Euphorbia antisyphilitica): Synergic of wax-polypropylene grafted Maleic anhydride - Marielli Elizabeth Ponce-Medina; Saúl Sánchez-Valdés; Marisela Estefanía Ángeles-San Martin; Homero Salas-Papayanopolos; Daniel Eugenio Hernández-Hernández; Tomas Lozano-Ramírez; Shervin Karami; Pierre LaFleur; Ana Beatriz Morales-Cepeda (Cogent Engineering, 2018)
Previous studies of Candelilla bagasse fiber (CBF) have demonstrated the improvement of fiber-polymer adhesion; in the present investigation, the CBF was used to reinforce fiber of Polypropylene composites varying the amount of fiber (0, 20 and 30 wt%), using Maleic anhydride as compatibilizer. The total wax of cuticle/intercuticular varies between 9.5 and 10.5 wt%; according to the TAPPI standard Polypropylene/candellia fiber, composites were realized with intercuticular wax. The amount of fiber of 20% and 30% varied in the composite, with and without compatibilizer. In this paper, we will demonstrate that this cuticular fiber wax acts in synergy with the composite in mechanical properties, mechanical dynamics analysis to observe adherence and in “cole-cole” diagrams.